Dinosaur census reveals abundant Tyrannosaurus and rare ontogenetic stages in the Upper Cretaceous Hell Creek Formation (Maastrichtian), Montana, USA. - John R Horner; Mark B Goodwin; Nathan Myhrvold (PLoS ONE, 2011)
A dinosaur census recorded during the Hell Creek Project (1999-2009) incorporates multiple lines of evidence from geography, taphohistory, stratigraphy, phylogeny and ontogeny to investigate the relative abundance of large dinosaurs preserved in the Upper Cretaceous Hell Creek Formation of northeastern Montana, USA. Overall, the dinosaur skeletal assemblages in the Hell Creek Formation (excluding lag-influenced records) consist primarily of subadult or small adult size individuals. Small juveniles and large adults are both extremely rare, whereas subadult individuals are relatively common. We propose that mature individuals of at least some dinosaur taxa either lived in a separate geographic locale analogous to younger individuals inhabiting an upland environment where sedimentation rates were relatively less, or these taxa experienced high mortality before reaching terminal size where late stage and often extreme cranial morphology is expressed.Tyrannosaurus skeletons are as abundant as Edmontosaurus, an herbivore, in the upper Hell Creek Formation and nearly twice as common in the lower third of the formation. Smaller, predatory dinosaurs (e.g., Troodon and dromaeosaurids) are primarily represented by teeth found in microvertebrate localities and their skeletons or identifiable lag specimens were conspicuously absent. This relative abundance suggests Tyrannosaurus was not a typical predator and likely benefited from much wider food choice opportunities than exclusively live prey and/or specific taxa. Tyrannosaurus adults may not have competed with Tyrannosaurus juveniles if the potential for selecting carrion increased with size during ontogeny.Triceratops is the most common dinosaur and isolated skulls contribute to a significant portion of this census. Associated specimens of Triceratops consisting of both cranial and postcranial elements remain relatively rare. This rarity may be explained by a historical collecting bias influenced by facies and taphonomic factors. The limited discovery of postcranial elements may also depend on how extensive a fossil quarry is expanded after a skull is collected.